Elemente neuer Bürgerlichkeit: Bourgeois und Citoyen in der postdemokratischen Elitenherrschaft - Salomon, David (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
The traditional characterization of the so called Black-Yellow coalition as a „bourgeois coalition“ elicited a broad debate over the relationship between citizens and bourgeoisie members. This debate was essentially characterized by a suppression of the connection between „bourgeois society“ and capitalism. The article recalls the relationship between “citoyen” and “bourgeois” and in this context reflects upon post-democratic attempts at „liberating“ capitalism from its vessels of democratic (class) representation. In this historic moment, citizen opposition alone will prove to be harmless. In defence of democracy it is of paramount importance to reestablish the concept of class as a political term.